Metabolic responses in melanoma cells to combined nutrient supplementation - Midgley, Nicola-Ann (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
This thesis examined the effect and biochemical mechanism by which combined vitamin E and C supplementation may influence tumour cell growth. The study initially addressed the effect of combined vitamin E succinate and Asc supplementation over a nutritional concentration range (5- 20μg/ml) and (25-50μg/ml) respectively, on the in vitro growth of non-malignant LLCMK and malignant BL6 cells. Supplementation of BL6 and LLCMK cells with combined vitamin E succinate and ascorbic acid, resulted in no significant increasing or decreasing trend in LLCMK cell growth, while in BL6 cells a significant decrease in cell growth was observed at all combined vitamin concentrations. It has been suggested that these vitamins may act synergistically to inhibit tumour cell growth through their antioxidant properties in quenching free radicals and lipid peroxidation and furthermore through their modulation of the activities of various enzymes and metabolites in the eicosanoid pathway. This study consequently investigated the effects of combined vitamin E succinate and ascorbic acid supplementation on these parameters. Throughout this study, emphasis was placed on the BL6 melanoma cells, as combined vitamin E succinate and ascorbic acid supplementation did not significantly affect growth or levels of secondary metabolites in the non-malignant LLCMK cells. Combined vitamin E succinate and ascorbic acid supplementation of BL6 cells resulted in a marked but non significant increase in free radical and a significant increase in lipid peroxidation levels. This prooxidant effect was accompanied by a significant decrease in BL6 cell growth, suggesting that the growth inhibitory effects of combined vitainin E succinate and ascorbic acid on BL6 cells in vitro was not mediated through their synergistic antioxidant properties. Vitamin E succinate is a nonphysiological antioxidant in its esterified form, hence cleavage of the succinate group must occur in order for ascorbic acid to interact with the free alcohol, vitamin E. The inability of combined vitamin E succinate and ascorbic acid to reduce free radicals and lipid peroxidation levels within BL6 cells may not be due to their ineffectiveness as antioxidants but rather the presence of other contributing factors which influence the oxidation state within the BL6 cells. Vitamin E is believed to modulate membrane-bound enzymes through membrane stabilization. Furthermore, the stabilizing effect of vitamin E may be enhanced by the ascorbic acid-sparing effect of vitamin E. Hence, this study investigated the effect of combined vitamin E succinate and ascorbic acid in modulating the activity of various enzymes and secondary messengers in the eicosanoid pathway. Supplementation with combined vitamin E succinate (5-20μg/ml) and ascorbic acid (25-50μg/ml) resulted in significant increases in phospholipase A₂, 5-lipoxygenase, cyclooxygenase and adenyl ate cyclase activity, with a significant decrease in BL6 cell growth. The possible synergistic action of these vitamins in terms of modulating membrane-bound enzymes was further substantiated by uptake and cellular distribution studies. Vitamin E succinate and vitamin E in the membrane fraction increased significantly compared to control cultures, while ascorbic acid levels were significantly higher in the stroma fraction when compared to membrane fractions. Consequently, another factor accounting for increased activities of phospholipase A2, 5-lipoxygenase and adenylate cyclase activities as a result of vitamin supplementation in BL6 cells may be an increased availability of Ca²+. Supplementation of BL6 cells with combined vitamin E succinate and ascorbic acid resulted in significant increases in intracellular Ca²+ levels at all combined vitamin groups. Furthermore, this increase in intracellular Ca²+ was positively correlated with cl1anges of the above-mentioned enzyme activities. Within the eicosanoid pathway, the rate of prostaglandin synthesis is regulated by phospholipase A₂ activity and arachidonic acid release, and the net prostaglandin production is dependent on cyclooxygenase activity, hence the effects of combined vitamin E succinate and ascorbic acid on arachidonic acid composition and prostaglandin production within BL6 cells was determined. The percentage arachidonic acid composition of the BL6 cells was elevated and inversely related to cell growth following combined vitamin E succinate and ascorbic acid supplementation. Prostaglandin E₂ and prostaglandin I₂ levels increased significantly, while those of prostaglandin D2 and prostaglandin F₂α increased markedly following supplementation of combined vitamin E succinate and ascorbic acid. These increases in prostaglandin levels were inversely related to BL6 cell growth, suggesting that the prostaglandins were involved in negative regulation of BL6 cell growth. When comparing the levels of prostaglandins, prostaglandin E2 levels were significantly higher when compared to prostaglandin D₂, prostaglandin F₂α and prostaglandin I₂ suggesting that vitamin E₂ succinate and ascorbic acid effects were mediated primarily through an increase in prostaglandin E2. Hence, prostaglandin E2 levels in combined vitamin E succinate and ascorbic acid appeared to be dependent on the amount of precursor present and the activity of its synthetic enzymes. This was confirmed when BL6 cells were supplemented with arachidonic acid. Arachidonic acid had an inhibitory effect on BL6 cell growth and also stimulated prostaglandin E₂ production. Prostaglandin E₂ levels are in turn believed to modulate adenylate cyclase activity in BL6 cells, hence it is reasonable to conclude that adenylate cyclase activity is dependent on prostaglandin E₂ levels. Combined vitamin E succinate and Asc supplementation to BL6 cells resulted in significant increases in adenyl ate cyclase and cyclic adenosine monophosphate, which again correlated with a significant decrease in cell growth. As cyclic adenosine monophosphate has a regulatory role in the cell cycle this study suggested that the effect of combined vitamin E succinate and ascorbic acid supplementation was mediated through the final effect provided by the second messenger, cyclic adenosine monophosphate. This was confirmed when BL6 cells were supplemented with dexamethasone, a phospholipase A₂ inhibitor. This treatment rsulted in combined vitamin E succinate and ascorbic acid having no inhibitory effect on BL6 cell growth. Cyclooxygenase activity, prostaglandin E₂ levels, adenylate cyclase activity and cyclic adenosine monophosphate levels were significantly lower in dexamethasone-treated cells compared to non-treated dexamethasone cultures. The reason for the increased free radical and lipid peroxidation levels in BL6 cells was further investigated. Cyclooxygenase enzymes are believed to generate free radical species during catalytic activity. Analysis of free radical and lipid peroxidation levels following supplementation with dexamethasone revealed markedly lower free radical and significantly lower lipid peroxidation levels in comparison with control cultures and non dexamethasone-treated cultures. These results suggest that the observed increases in free radical and lipid peroxidation levels in BL6 cells supplemented with combined vitamin E succinate and ascorbic acid were indirectly due to the increase in cyclooxygenase activity in these cells.
Keywords: Melanoma; Tumors -- Growth